Utilities and Limitations of the World Health Organization 2009 Warning Signs for Adult Dengue Severity - Thein, Tun-Linn (Public Library of Science, 2013)
BACKGROUND: In 2009, the World Health Organization (WHO) proposed seven warning signs (WS) as criteria for hospitalization and predictors of severe dengue (SD). We assessed their performance for predicting dengue hemorrhagic fever (DHF) and SD in adult dengue. METHOD: DHF, WS and SD were defined according to the WHO 1997 and 2009 dengue guidelines. We analyzed the prevalence, sensitivity (Sn), specificity (Sp), positive predictive value (PPV) and negative predictive value (NPV) of WS before DHF and SD onset. RESULTS: Of 1507 cases, median age was 35 years (5(th)–95(th) percentile, 17–60), illness duration on admission 4 days (5(th)–95(th) percentile, 2–6) and length of hospitalization 5 days (5(th)–95(th) percentile, 3–7). DHF occurred in 298 (19.5%) and SD in 248 (16.5%). Of these, WS occurred before DHF in 124 and SD in 65 at median of two days before DHF or SD. Three commonest warning signs were lethargy, abdominal pain/tenderness and mucosal bleeding. No single WS alone or combined had Sn >64% in predicting severe disease. Specificity was >90% for both DHF and SD with persistent vomiting, hepatomegaly, hematocrit rise and rapid platelet drop, clinical fluid accumulation, and any 3 or 4 WS. Any one of seven WS had 96% Sn but only 18% Sp for SD. CONCLUSIONS: No WS was highly sensitive in predicting subsequent DHF or SD in our confirmed adult dengue cohort. Persistent vomiting, hepatomegaly, hematocrit rise and rapid platelet drop, and clinical fluid accumulation, as well as any 3 or 4 WS were highly specific for DHF or SD.